Wearable mobile internet devices involved in big data solution for education. (2016) - Sun, Aobing; Ji, Tongkai; Wang, Jun; Liu, Haitao
The big data in education faces one methodology problem, i.e., how to acquire, store and apply the big data, especially to find one mediator to associate and solve the problem overall. In this paper, we create our big data model for one school firstly, which includes the behaviour subject information model and its related activity model. The behaviour subjects include the school, class, teacher, students, parents, etc. The information model relates with the subjects' basic and the activity information. Secondly, the collection means of big data is presented, the detailed big data about the activities are acquired from the existing and extended school information systems, e.g., as the administration systems for student attendance, quiz, shopping, etc. Thirdly, the wearable mobile internet devices act as one new means to provide more information and one key to associate different data from heteronomous sources. Finally, we verify our big data model through new applications, such as school-bus route optimisation, timecost impact to learning, and parents' affection for students' development, etc.